2016
DOI: 10.30957/ijoltl.v1i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Illocutionary and Perlocutionary Acts on Main Characters Dialogues in John Milne’s Novel: “ the Black Cat”

Abstract: This article describes the types of illocutionary acts and the impact of perlocutionary acts on main characters’ dialogues in John Milne’s Novel: The Black Cat”. This study used descrpitive qualitative design. Data of this study were  dialogues in the “The Black Novel”. The study revealed that the dialogue posses five types of illocutionary acts i.e. declaratives, assertives, expressive, directives, commissives and the impact of perlocutionary act. Readers can broaden and enrich the knowledge of speech acts es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…Speech act is the utterances which occur between the people who are communicating. It is a part of language that concerns in what people say trough the language (Yule, 1996;Kim & Lee, 2015;Nurhayati & Yuwartatik, 2016;Woods, 2016;Ogleznev, 2016;Suhirman, 2016;Petrey, 2016;Sameer, 2017;Marzuki, 2017;Kravchenko, 2017;Mufiah & Rahman, 2019). Speech act is identified as an approach of conceptualizing argumentative activities such as those in daily-life.…”
Section: Introductionmentioning
confidence: 99%
“…Speech act is the utterances which occur between the people who are communicating. It is a part of language that concerns in what people say trough the language (Yule, 1996;Kim & Lee, 2015;Nurhayati & Yuwartatik, 2016;Woods, 2016;Ogleznev, 2016;Suhirman, 2016;Petrey, 2016;Sameer, 2017;Marzuki, 2017;Kravchenko, 2017;Mufiah & Rahman, 2019). Speech act is identified as an approach of conceptualizing argumentative activities such as those in daily-life.…”
Section: Introductionmentioning
confidence: 99%
“…The representative/assertive was mostly found. Nurhayati and Yuwartatik (2016) studied illocutionary and perlocutionary, acts on main characters dialogues in John Milne's novel: The Black Cat. The study revealed that the dialogue possessed five types of illocutionary acts proposed by Searle (1969): declarative, assertive, expressive, directives, commissives.…”
Section: Introductionmentioning
confidence: 99%
“…There are some previous studies related to this research. Nurhayati & Yuwartatik (2016) investigated the illocutionary act types and the impacts of perlocutionary act performed by the main characters in a science-fiction novel. The results showed that all of the five illocutionary act types occurred in the novel.…”
Section: Introductionmentioning
confidence: 99%